Cardiorespiratory fitness in adolescents and young adults with Klinefelter syndrome – a pilot study - Spiekermann, Julia; Sinningen, Kathrin; Hanusch, Beatrice; Kleber, Michaela; Schündeln, Michael M.; Kiewert, Cordula; Siggelkow, Heide; Höppner, Jakob; Grasemann, Corinna (Frontiers in Endocrinology, 2023)
Background Klinefelter syndrome (KS) may be associated with a wide spectrum of phenotypic changes including endocrine, metabolic, cognitive, psychiatric and cardiorespiratory pathologies in adults. However, in adolescence the clinical phenotype of KS is not well described, especially regarding physical fitness. The present study reports on cardiorespiratory function in adolescents and young adults with KS. Methods Adolescents and young adults with KS were recruited in a cross-sectional pilot study. Biochemical parameters of fitness including hormonal status, a body impedance analysis, the grip strength, the amount of physical activity at home for 5 days via trackbands and anamnestic parameters were assessed. In addition, participants underwent an incremental symptom-limited cardiopulmonary exercise test (CPET) on a bicycle ergometer. Results Nineteen participants with KS aged 15.90 ± 4.12 years (range: 9.00 - 25.00) participated in the study. Pubertal status was Tanner 1 (n = 2), Tanner 2 - 4 (n = 7) and Tanner 5 (n = 10). Seven participants received testosterone replacement therapy. Mean BMI z-score was 0.45 ± 1.36 and mean fat mass was 22.93% ± 9.09. Grip strength was age-appropriate or above normal. 18 participants underwent CPET with subnormal results for maximum heart rate (z-score -2.84 ± 2.04); maximum workload (Wattmax; z score -1.28 ± 1.15) and maximum oxygen uptake per minute (z- score -2.25 ± 2.46). Eight participants (42.1%) met the criteria for chronotropic insufficiency (CI). Data from track-bands showed sedentary behavior for 81.15% ± 6.72 of the wear time. Conclusion A substantial impairment of cardiopulmonary function can be detected in this group of boys to young adults with KS, including chronotropic insufficiency in 40%. The track-band data suggest a predominantly sedentary lifestyle, despite normal muscular strength as assessed via grip strength. Future studies need to investigate the cardiorespiratory system and its adaption to physical stress in a larger cohort and in more detail. It is feasible that the observed impairments contribute to the avoidance of sports in individuals with KS and may contribute to the development of obesity and the unfavorable metabolic phenotype.